The Effectiveness of ECE (Early Clinical Exposure) on the Integration of Basic Knowledge with Type 2 Diabetes Mellitus Clinical Knowledge and Interprofessional Collaboration in Medical Students of Prima Indonesia University - Bella Sari Sijabat; Clarissa Lister; Edy Fachrial (Al-Makki Publisher, 2024)
Early Clinical Exposure (ECE) is a teaching-learning methodology that involves exposing medical students to patients or clinical scenarios early in the first year of medical education. In this study, the focus is on fifth-semester students, particularly on the integration of basic knowledge with clinical knowledge of Type 2 Diabetes Mellitus (DMT2), the role of multidisciplinary teams, and interprofessional collaboration. The purpose of this study is to determine the effectiveness of early clinical exposure in integrating basic knowledge with clinical knowledge of DMT2 and knowledge of interprofessional collaboration among medical students at Universitas Prima Indonesia. The method used in this research is a quantitative approach with an experimental design, specifically quasi-experimental research. In this design, 124 fifth-semester medical students from Universitas Prima Indonesia will be given a pretest before participating in Early Clinical Exposure (ECE) and a posttest after completing Early Clinical Exposure (ECE). The results of this study indicate a significant difference in the integration of basic knowledge with clinical knowledge of DMT2 and knowledge of interprofessional collaboration among medical students at Universitas Prima Indonesia, with a p-value of 0.000 (p < 0.05). Therefore, it can be concluded that Early Clinical Exposure (ECE) is effective in improving the integration of basic knowledge with clinical knowledge of DMT2 and knowledge of interprofessional collaboration among medical students at Universitas Prima Indonesia.